Severe maternal morbidity among migrants with insecure residency status in Sweden 2000-2014: a population-based cohort study - Can Liu; Elizabeth Wall-Wieler; Marcelo Urquia; Suzan L. Carmichael; Olof Stephansson (Elsevier, 2020)
Background: Migrants with insecure residency status (i.e., undocumented migrants and asylum-seekers, who are denied or waiting for authorized residency) often experience social and psychosocial adversities and limited access to health care. Nonetheless, they have not been profiled on the risk of severe maternal morbidity (SMM), a sentinel measure of maternal health and maternity care. Methods: A cohort study on all births recorded in the Swedish Medical Birth Register from 2000-2014 (N = 1,570,472). Lacking a maternal personal identification number was used as an indicator for insecure residency status (1.3% of all births). We used Poisson regression models to estimate risk ratios of SMM in migrant women with insecure residency status compared to the Swedish-born or migrant women with long-term residency, adjusting for the calendar year of birth, maternal age, and parity. Results: Overall SMM rate among migrant women with insecure residency status was 21.5/1000 and 14.7/1000 among Swedish-born women. Compared to Swedish-born, migrants with insecure residency status had 50% higher risk of overall SMM (adjusted risk ratio (aRR)=1.54 [1.37-1.74]) and over 80% higher risk of SMM excluding transfusion-only cases (aRR=1.88 [1.37-2.57]). When compared to migrant women with long-term residency, migrant women with insecure residency also had a higher risk of SMM (overall SMM aRR=1.42 [1.26,1.61]; SMM excluding transfusion only cases aRR=1.43 [1.04,1.97]), suggesting that insecure residency conferred additional risks of SMM beyond migration. Conclusion: Migrant women with insecure residency status had increased risk of severe maternal morbidity.